Batwa Indigenous Peoples forced eviction for "Conservation": A qualitative examination on community impacts. - Sylvia Kokunda; Haven Nahabwe; Jeremiah Nahamya; Samari Niwamanya; Ronald Mazirwe; Samrawit Gougsa; Elizabeth Kemigisha; Nicole Redvers (Public Library of Science (PLoS), 2023)
In 1991, the Ugandan government formally established National Parks within the ancestral homelands of the Batwa Peoples. No consultation was carried out with local Batwa communities, and they were consequently forcibly evicted from their Forest home. With this, we sought to better understand the impacts of forced Land eviction through the lens of solastalgia. Nineteen semi-structured interviews were carried out with adult Batwa Peoples of varying age and gender in Uganda from August to November 2022. Interviews were transcribed verbatim, and thematic analysis was carried out on the interview transcripts to identify themes from the initial codes. Four overarching themes were identified, including: 1) Our love and connection with the Forest; 2) What was left in the Forest when we were evicted; 3) What eviction from the Forest did to us as Batwa Peoples; and 4) Batwa People's Landback and returning to the Forest ('Indigenous Lands back into Indigenous hands'). As movement towards the global "30 by 30" conservation agenda occurs, we urge researchers, policy makers, and leaders to listen to the voices of Indigenous Peoples like the Batwa with a key focus on Landback and movement towards a clearer understanding and appreciation of the impacts of Western conservation agendas on Indigenous Peoples globally.